Infantile Amoebiasis: A Case Report. (21st June 2012) - Zibaei, Mohammad; Firoozeh, Farzaneh; Azargoon, Alireza
Abstract : Amoebiasis continues to be a major cause of morbidity and mortality in children in developing countries. Entamoeba histolytica infections are commonly observed in tropical and subtropical regions of the world including Iran. In developed countries Entamoeba histolytica infections are commonly seen in travelers, recent immigrants, homosexual men, and inmates of institutions. The disease is more severe in the two extremes of life. This paper paper describes a four-month-old male infant with Entamoeba histolytica presenting initially with refusal of feeds, hyperactive bowel sound, vomiting, and diarrhea. A fecal sample was positive for Entamoeba histolytica by Lugol's iodine solution and the concentration technique. He was successfully treated with metronidazole for 5 days. This case illustrates that Entamoeba species could be pathogenic in young infant; therefore, awareness of the infection, aggressive approach to diagnosis, and early initiation of treatment continue to be critical component of infection control.